PENGARUH LOYALITAS, PENDIDIKAN DAN PELATIHAN SERTA KINERJA TERHADAP PROMOSI JABATAN PADA KANTOR SEKRETARIAT DAERAH KABUPATEN TOLITOLI - Mirayanti, Mirayanti (Katalogis, 2015)
The objective of this research are to know and analyze the effects of loyalty, education, training and performane on promotion at regional secretariat, Tolitoli regency.(2) to know and analyze the effectof loyalty and promotion, (3) o know and analyze the effect of education and training on promotion, (4) to know and analyze the effect of performanceon promotion at regional secretariat, Tolitoli regency. This is a causal discriptive research to investigate the relationships among variables involing 99 respondents that have been tetermined using census method. The result of multiple Linear regresion show that : (1) loyalty, education, training, and performance simultaneously perform significant effects on promotion, (2) loyalty performance significant effect on promotion, (3) educatin and training perform significant effect on promotion, (4) performance performs significant effect on promotion at regional secretariat, Tolitoli Regency.